PENGARUH DIGITALISASI UMKM DAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA UMKM PADA MASA PANDEMI COVID-19 - Ezra Syamir Suhargo; Yusriyati Nur Farida; Taufik Hidayat (Jurnal Riset Akuntansi Soedirman (JRAS), 2022)
This study aims to determine the effect of knowledge, accounting information systems, digital marketing and payment gateways on the performance of MSMEs during the COVID-19 pandemic. This study uses primary data, with a population of MSME in Banyumas Regency. The sampling technique used purposive sampling method, and required a sample of 100 samples. In this study, the technical analysis of the data used was pilot test, descriptive statistical test, data quality test, classical assumption test, multiple linear regression analysis and statistical hypothesis testing. The results of the study stated that: (1) the accounting information system had no effect on improving the performance of MSMEs during the COVID-19 pandemic; (2) digital marketing has no effect on improving the performance of MSMEs during the COVID-19 pandemic; (3) payment gateways have no effect on improving the performance of MSMEs during the COVID-19 pandemic. The implication of this research is that MSME can find out the factors that really affect to MSME performance, especially after the COVID-19 pandemic and also for the Banyumas Regency Governance, Cooperatives and MSMEs Office to provide education and training for MSMEs so their performance can improving and increasing.